1993
DOI: 10.1016/s0022-5347(17)36045-7
|View full text |Cite
|
Sign up to set email alerts
|

Female Urinary Tract Fistulas

Abstract: Urinary tract fistulas in women are an uncommon complication of a variety of surgical procedures. However, such fistulas lead to significant patient and physician distress, and have important medicolegal implications. Successful repair of urinary tract fistulas requires careful preoperative evaluation and adherence to basic surgical principles. A variety of approaches and techniques may be used, and the choice of procedure is less important than achieving adequate resection of fibrosis with watertight, tension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
4

Year Published

1995
1995
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(43 citation statements)
references
References 67 publications
0
38
0
4
Order By: Relevance
“…In another series, four patients who developed a fistula after abdominal and vaginal hysterectomy were treated with bladder drainage for periods of 19-54 days; all remained dry after the removal of the catheter [14]. It has been suggested that if healing has not occurred within 4 weeks, it is unlikely that a fistula will close spontaneously [15].…”
Section: Discussionmentioning
confidence: 99%
“…In another series, four patients who developed a fistula after abdominal and vaginal hysterectomy were treated with bladder drainage for periods of 19-54 days; all remained dry after the removal of the catheter [14]. It has been suggested that if healing has not occurred within 4 weeks, it is unlikely that a fistula will close spontaneously [15].…”
Section: Discussionmentioning
confidence: 99%
“…Vesicovaginal fistulas are the most common fistula in the urinary system [3], and their etiology varies in different nations. In developed countries, at least 75% of vesicovaginal fistulas are caused by pelvic operations of gynecology, urology, and others, with obstetric operations making up most of the operational causes.…”
Section: Discussionmentioning
confidence: 99%
“…It seems that to be successful the catheter treatment should last up to 2 months. However, in some recent reports early closure has been suggested [13,14]. Probably this is reasonable when considering how troublesome continuous urinary leakage is for the patient.…”
Section: Discussionmentioning
confidence: 99%